TEACHING THE GRATEFUL DEAD, HAPPENINGS, & SPONTANEOUS PEDAGOGY - Slesinger, Ryan (Dialogue, 9(1,2), 2022)
To teach a course on the Grateful Dead I developed a praxis I call “spontaneous pedagogy” that pairs academic rigor with flexible curriculum details to enable creativity and engagement among students in a truly student-centered classroom. The pairing of spontaneous pedagogy with the Grateful Dead course worked well because the subject emphasizes improvisation, which initially inspired and—during the course—paralleled my praxis. I had developed this praxis previously, implementing it each semester from 2007 to2010 for one Composition II unit on definitional arguments entitled, “The Nature of Reality.” Students were asked to define what they consider as real and apply that definition to a mythological creature. Utilizing spontaneous pedagogy in this unit was successful: students gained agency in the classroom, guiding our activities towards topics that were important topics for them, and produced unique and excellent work. Following this success, I taught a topic-based intersession class (80 hours in three weeks) on the Grateful Dead in 2011, relying on spontaneous pedagogy and allowing students more agency to determine our curriculum. But something unusual happened: as the students determined the topics for class discussion, they also began assigning themselves additional homework and reading tasks, including their own essay assignments and their submission of their own oral and multimodal presentations on topics of their choosing. I found that spontaneous pedagogy in the Grateful Dead classroom achieved a truly student-centered learning experience as students willingly took over the roles of curriculum and assignment design, leaving me to prepare the classes and participate in them as a guide. In addition to the knowledge of the topic students gained in the class, they also gained a unique experience of a spontaneous atmosphere in an academic setting that paralleled a Grateful Dead improvisation or show experience. Keywords: Grateful Dead, Geoffrey Sirc, Charles Deemer, happening, pedagogy, improvisation, epiphany, agency, spontaneous pedagogy, student-centered pedagogy
Keywords: Type of access: Open Access